Preferences of a Traditional Extension Audience for Self-Directed Delivery Methods - Allen E. Caldwell; John G. Richardson (Journal of Applied Communications, 1995)
Nearly all farmers of burley in the mountains of North Carolina are small or part-time growers who have limited time for seeking information.